WEST AFRIKA: MUSIKGESCHICHTE IN BILDERN, by Gerhard Kubik, VEB Deutscher Verlag fur Musik, Leipzig, 1989, Band I, Musikethnologie, Lieferung 11, ed. Werner Bachmann, 222pp, illustrations, appendix, bibliography. - Erlmann, Veit (International Library of African Music, 1996)
pages: 104-105
Keywords: African Music